Cleavage of exosomal-associated transferrin receptor in dogs, cats, and horses: progress towards a soluble transferrin receptor assay - Martinez, Caitlyn Marisa Romero, author; Olver, Christine, advisor; Santangelo, Kelly, advisor; Duval, Dawn, committee member (Colorado State University. Libraries, 2018)
Iron deficiency anemia and anemia of chronic disease are two complications that patients in human medicine as well as veterinary medicine often encounter. These two diseases usually occur secondary to other primary diseases and are associated with increased morbidity and a decline in prognosis. The diagnosis and differentiation of these diseases is complicated by the fact that many of the parameters used to characterize iron deficiency are also influenced by inflammatory cytokines. Consequently, the detection of iron deficiency in the presence of inflammation or the detection of combined iron deficiency anemia and anemia of chronic disease is difficult. Differentiation of these two diseases is important as treatment for each disease is different and potentially harmful if utilized on a patient who has been misdiagnosed with one disease or the other. In human medicine, soluble transferrin receptor 1 (sTfR) has shown promise as a marker, alone or in ratio with serum ferritin, that can differentiate iron deficiency anemia, anemia of chronic disease, and combined disease. sTfR is the product of cleavage of transferrin receptor 1 (TfR1) from the surface of exosomes which are released into circulation from maturing reticulocytes. Humans cleave the majority of their exosomal-associated TfR1 yielding substantial levels of circulating sTfR for detection and quantification by clinical assays. However, the level of cleavage in many of our veterinary species, including dogs, cats, and horses, remains unknown. Additionally, no currently developed sTfR clinical assays have been found to successfully detect sTfR in our veterinary species. The purpose of this study was to first confirm the presence of exosomes and exosomal-associated TfR1 in the serum of dogs, cats, and horses. Secondly, the level of cleavage of exosomal-associated TfR1 in healthy dogs, cats, and horses was explored to indirectly characterize the anticipated levels of circulating sTfR in these species. Lastly, the level of cleavage of exosomal-associated TfR1 was compared between healthy and diseased dogs and cats to investigate any potential effect of inflammation and chronic disease on the cleavage of exosomal-associated TfR1 and thus on the anticipated levels of circulating sTfR. The results of this study demonstrated significant evidence indicating the successful isolation of exosomes and identification of exosomal-associated TfR1 from the serum of dogs, cats, and horses. The level of cleavage of exosomal-associated TfR1 in dogs was found to be greater than 50% on average with significant between-individual variation. There was also no significant difference in the means of the proportion of cleavage between healthy and diseased dogs. The level of cleavage of exosomal-associated TfR1 in cats was found to be very low at about 11% without substantial variation between individuals. However, a small but significant difference between healthy and diseased cats was detected. Healthy horses do not appear to cleave exosomal-associated TfR1. These results together would suggest that development of a clinical assay for the detection and quantification of sTfR in these veterinary species may not be successful and consequently may not be worth the time, effort, and expense.
Keywords: cats; exosomes; transferrin receptor; dogs; anemia of chronic disease; iron deficiency anemia